Trypanosoma cruzi Parasite Load Modulates the Circadian Activity Pattern of Triatoma infestans - Francisco Chacón; Catalina Muñoz-San Martín; Antonella Bacigalupo; Bárbara Álvarez-Duhart; Rigoberto Solís; Pedro E. Cattan (Insects, 2022)
American trypanosomiasis is a disease caused by the flagellate protozoan Trypanosoma cruzi, which is transmitted mainly in endemic areas by blood-sucking triatomine vectors. Triatoma infestans is the most important vector in the southern cone of South America, exhibiting a nocturnal host-seeking behavior. It has been previously documented that the parasite produces changes in some triatomine species, but this is the first time that the behavior of a vector has been evaluated in relation to its parasite load. After comparing the movement events and distance traveled of infected and non-infected T. infestans, we evaluated the change produced by different T. cruzi parasite loads on its circadian locomotor activity. We observed differences between infected and non-infected triatomines, and a significant relation between the parasite load and the increase in locomotor activity of T. infestans, which was accentuated during the photophase. This could have direct implications on the transmission of T. cruzi, as the increased movement and distance traveled could enhance the contact of the vector with the host, while increasing the predation risk for the vector, which could both constitute a risk for vectorial and oral transmission to mammals.